Screening of local landraces of rice (Oryza sativa L.) at the seedling stage for salinity tolerance based on genetic divergence analysis - Ara, Iffat; Rasel, Md; Hassan, Lutful; Islam, Mirza Mofazzal; Injamum-Ul-Hoque, Md (Fundamental and Applied Agriculture, 2019)
The presence of genetic diversity is a prerequisite for improvement of any crops. Salinity is a severe threat for the production of rice which can be solved by improving tolerant variety through breeding programs. Twenty-five rice genotypes were evaluated to explore the genetic diversity of growth param- eters by imposing three levels of salinity treatments (0 dS m−1, 7 dS m−1 and 12 dS m−1 EC) with three replications following completely randomized design (CRD).The genotypes were categorized into five major sub-clusters considering ten morphological traits using the non-hierarchical Euclidean distances revealed that maximum 10 genotypes viz., Moynamoti, Badshavog, Pangash, Suvash, Moghabalam, Sadaswarna, Binadhan-8, Chinikani, Ashfailand, and Rajashail were found in cluster III while lowest two genotypes namely Lalbat and M-171 were found in cluster IV. The results of the cluster analysis also reported that the intercluster distances in all the cases were greater than the intra-cluster distances. The highest intra-cluster diversity was observed in cluster IV (6.30) whereas lowest intra-cluster diversity was found in cluster I (4.16). The maximum inter-cluster distance was found between cluster II and V (15.45) where minimum inter-cluster distance was observed between cluster I and II (6.39). Root fresh weight contributed great- est (19%) to the divergence of genotypes where root length contributed least (0.33%) to the total diversity of the genotypes. The cluster means value for most of the morphological traits was maximum in cluster II reflecting that the genotypes grouped in cluster II could be selected as salt tolerant genotypes at the seedling stages for the cultivation in the coastal area of Bangladesh.